BRAC's pilot savings project of RDP: monitoring and evaluation - Moore, Karen J.; Choudhury, M. Sadiqunnabi (BRAC, 2019)
During July and August of 1996, the BRAC Rural Development Programme (RDP) initiated a Pilot Savings Project (PSP), whereby three experimental savings systems were implemented in various areas of Bangladesh, with a proposed lifespan of two to three years. The BRAC Research and Evaluation Di-vision (RED) undertook to develop a monitoring and evaluation process for the PSP. This paper documents the first stages of this process and presents current research and experience on the topic. It is in particular aimed at BRAC-RED staff who are interested in continuing work on PSP monitoring, and BRAC-RDP staff involved with the management of the programme. This paper is in general concerned with BRAC's transition from an NGO involved in microcredit, to one at the forefront of the movement to provide flexible, appropriate, transparent, and clear financial services to the poor.